Sources of Displaced Workers’ Long-Term Earnings Losses - Lachowska, Marta; Mas, Alexandre; Woodbury, Stephen A. (American Economic Review, 2020)
We estimate the magnitudes of reduced earnings, work hours, and wage rates of workers displaced during the Great Recession using linked employer-employee panel data from Washington state. Displaced workers’ earnings losses occurred mainly because hourly wage rates dropped at the time of displacement and recovered sluggishly. Lost employer-specific premiums explain only 17 percent of these losses. Fully 70 percent of displaced workers moved to employers paying the same or higher wage premiums than the displacing employers, but these workers nevertheless suffered substantial wage rate losses. Loss of valuable specific worker-employer matches explains more than one-half of the wage losses. (JEL E32, J22, J31, J63, R23)